Peroxisome proliferator-activated receptors as molecular targets in relation to obesity and type 2 diabetes - Seda, Ondørej; Sedová, Lucie (Pharmacogenomics, 2007)
The three isotypes of peroxisome proliferator-activated receptors (PPARs) are currently perceived as major regulatory nodes (or hubs) of metabolic pathway networks, linking most prevalent diseases including Type 2 diabetes, obesity, dyslipidemia and atherosclerosis. The integrative functions of PPARs are also reflected in their ecogenetic profile, when the variants underlying pharmacogenetic interactions were also shown to modulate the effect of lifestyle factors. Despite their extensive clinical use, there are many outstanding issues, especially concerning their safety. Critical pharmacogenomic assessment is warranted for the new potent ligands of multiple PPAR isoforms as many have displayed serious side-effects in a limited number of treated subjects. Nevertheless, the advent of genomic, transcriptomic and system biology-level approaches, integrating knowledge from model systems and human biology, should greatly facilitate the transition to individualized PPAR-based therapies.
Keywords: obezita; Diabetes Mellitus, Type 2; genetická variace; Genetic Variation; Obesity; Animals; Anti-Obesity Agents; Humans; Gene Targeting; látky proti obezitě; lidé; diabetes mellitus 2. typu; Drug Delivery Systems; zvířata; Peroxisome Proliferator-Activated Receptors; lékové transportní systémy; receptory aktivované proliferátory peroxizomů; genový targeting